Pour un féminisme critique - Braidotti, Rosi (Les Cahiers du GRIF, 1983)
http://www.persee.fr/web/revues/home/prescript/article/grif_0770-6081_1983_num_28_1_1398
Keywords: 1900-1999; 1980-1989; cours; cycles supérieurs; discipline; fem9000; philosophie; périodes historiques; ressource en ligne; sciences humaines

The Anti-aesthetic: essays on postmodern culture - Foster, Hal (Bay Press, 1983)
For the past thirty years, Hal Foster has pushed the boundaries of cultural criticism, establishing a vantage point from which the seemingly disparate agendas of artists, patrons, and critics have a telling coherence. In The Anti-Aesthetic, preeminent critics such as Jean Baudrillard, Rosalind Krauss, Fredric Jameson, and Edward Said consider the full range of postmodern cultural production, from the writing of John Cage, to Cindy Sherman's film stills, to Barbara Kruger's collages. With a redesigned cover and a new afterword that situates the book in relation to contemporary criticism, The Anti-Aesthetic provides a strong introduction for newcomers and a point of reference for those already engaged in discussions of postmodern art, culture, and criticism. Includes a new afterword by Hal Foster and 12 black and white photographs.
Le texte suivant : Owens, Craig. (1983). The Discourse of Others: Feminists and Postmodernism, 57-82 a été donné en lecture au cours HAR4600.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; approches et analyses; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; postmodernisme; premier cycle; périodes historiques; thématiques

La lutte pour le droit à l’avortement (1969-1981) - Lamoureux, Diane (Revue d'histoire de l'Amérique française, 1983)
Number: 1 https://id.erudit.org/iderudit/304126ar
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amérique du nord; amériques; avortement; canada; discipline; front de libération des femmes; histoire; justice reproductive; militance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques

La Québécoite: roman - Robin, Régine (Québec-Amérique, 1983)
Sous le regard de l'Autre. Par l'auteure d'Histoire et linguistique (Colin, 1973) et d'une étude sur l'écriture juive (Le Sorbier, 1983), un récit dans lequel ce professeur d'université française, d'origine judéo-russe, qui enseigna à Montréal, Laval et Sherbrooke relate, pour le bénéfice de ses étudiants, l'histoire de sa découverte du Québec entre 1974 et 1981. Régine Robin, de formation marxiste, manifeste une attention particulière aux luttes ouvrières (grèves, etc.), politiques, idéologiques. L'éditeur parle avec justesse d'un livre d'émigrante sur l'exil, la langue et la vie d'ici. Composition en mosaïque. Inventaires, comparaisons, fragments, altérités.
Section: 200 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; cours; discipline; disicpline; histoire et politique; immigration; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires